Mentalne wzorce relacyjne jako predyktory statusu związku studiujących kobiet - Soroko, Emilia; Adamczyk, Katarzyna; Klepka, Paweł; Jankowiak, Barbara (Wydawnictwo Naukowe UAM, 2018)
The article analyses relationship patterns as predictors of relationship status (having vs not having a partner) among female university students. Inner relationship patterns were identified on the basis of written statements on significant relations. The statements were obtained through the Relationship Anecdotes Paradigm (RAP), which allows the acquisition of autobiographic records of narrative nature on personally significant interpersonal relations. The results of the analysis based on the concept of Core Conflictual Relationship Theme (CCRT) helped predict whether a respondent has a partner thanks to only one category of relationship patterns – the desire of the self to feel well and comfortably, to have a sense of stability, to feel happy and self-satisfied, triggered in the context of referring to a significant interpersonal relation in the narratives. The other aspects of the patterns – responses of the other to the self’s desire and the response of the self to the reactions of the other – do not markedly affect the prediction of the relationship status.
Mental Relationship Patterns as Predicators of the Relationship Status of Studying Women
Keywords: relation patterns; singles; relationship status; Core Conflictual Relationship Theme (CCRT), Relationship Anecdotes Paradigm (RAP)